Justifying reality in fatwa, ijtihad, and submission to its influence and some of its contemporary applications - Ihsan Alo Hussein (Islamic Sciences Journal, 2024)
ABSTRACT The “reality” in which we live, whether social, economic, intellectual, scientific, or cultural, has a major role in determining many partial legal rulings and in changing fatwas. However, we notice some wrong fatwas that are far from the spirit of Islamic legislation, issued and still being issued by some of those who oppose the fatwa. Under the pretext of justifying the reality in which we live, the truth is ignorance of the purposes of Islamic law, which came to achieve interests, prevent harm, build humanity, and seek the pleasure of God Almighty. Whoever neglects to consider the purposes of Sharia law falls into confusion and confusion, and makes deviant statements that contradict the purposes of Sharia law, so the mufti must issue his fatwa according to a disciplined approach in understanding reality and understanding the legal rulings that he applies to the new facts.